1991
DOI: 10.1159/000158839
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides as Cotransmitters in Vascular Sympathetic Neuroeffector Transmission

Abstract: Postganglionic sympathetic cotransmission by noradrenaline (NA) and adenosine 5’-triphosphate (ATP) was studied in isolated arteries from rabbits using as tools α-adrenoceptor antagonists and αβ-methylene-ATP which first activates and then desensitizes purine P2X receptors. In the pulmonary artery, NA was the only chemical signal responsible for neurogenic vasoconstriction. In sharp contrast, ATP was the only signal eliciting electric as well as mechanical postjunctional responses in small jejunal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…First, it can be released from primary afferent nerves themselv es (Holton, 1959). There is also much evidence for ATP release from sympathetic nerves, where it appears to be copackaged with noradrenaline (Sneddon & Burnstock, 1984; Starke et al 1991; Evans & Surprenant, 1992). In some of these cases ATP is the main neuro‐effector transmitter, such as the innervation of the vas deferens and some arteriolar smooth muscle.…”
Section: Atp Is Released By Damaged Tissue?mentioning
confidence: 99%
“…First, it can be released from primary afferent nerves themselv es (Holton, 1959). There is also much evidence for ATP release from sympathetic nerves, where it appears to be copackaged with noradrenaline (Sneddon & Burnstock, 1984; Starke et al 1991; Evans & Surprenant, 1992). In some of these cases ATP is the main neuro‐effector transmitter, such as the innervation of the vas deferens and some arteriolar smooth muscle.…”
Section: Atp Is Released By Damaged Tissue?mentioning
confidence: 99%
“…Numerous studies on blood vessels provide evidence for sympathetic cotransmission of NA and ATP (Ramme et al, 1987; for review see Burnstock & Kennedy, 1986;Burnstock, 1988;Ralevic & Burnstock, 1991b). Depending on the kat PPADS selectively species, the type of blood vessel, the stimulation pattern responses in the rat (frequency, duration of stimulation) and the temperature at which experiments are carried out, the one or other transmitter dominates (Burnstock, 1988;Starke et al, 1991;Yamamoto et al, 1992). Cotransmission of NA and ATP has been shown in isolated small mesenteric arteries (Sjoblomare mediated via al- Widfeldt, 1990;Sj6blom-Wildfeldt et al, 1990) and under oth muscle of the rat certain conditions in the isolated whole mesenteric arterial al., 1990), remained bed preparation (Yamamoto et al, 1988;1992).…”
Section: Ppads With A-adrenoceptors Couldmentioning
confidence: 99%
“…Many studies of sympathetic co-transmission, including ATP and NA, have now also been carried out on a number of different isolated blood vessels [see Burnstock, 1988;Schwartz and Malik, 1989;Starke et al, 1991;Evans and Surprenant, 19921. Sympathetic co-transmission involving NA and ATP has also been shown in the circulation of skeletal muscle, intestine [Taylor and Parsons, 19891, kidney [Schwartz and Malik, 19891, and skin, as well as in the pithed rat [ Bulloch and McGrath, 1988;Schlicker et al, 19891. Recent studies in my laboratory have shown that, in rabbit coronary vessels, in contrast to other vessels where NA and ATP cause synergistic constriction via a,-adrenoceptors and P,,-purinoceptors, respectively, the predominant effect of ATP is vasodilatation via P,,-purinoceptors [Corr and Burnstock, 19911. Since in this vessel the predominant effect of NA is vasodilatation via P-adrenoceptors, this is consistent with the synergism that appears to be characteristic of co-transmission.…”
Section: Sympathetic Neurotransmissionmentioning
confidence: 99%